Kant's theory of biology - Goy, Ina, 1972-; Watkins, Eric, 1964- (De Gruyter, 2014)
Kant's theory of biology has emerged as an important field of study within Kant scholarship. The volume Kant's Theory of Biology contains 15 essays by leading international Kant scholars and philosophers of biology. Topics discussed include 17th- and 18th-century biological theories, the development of Kant's views on biology, the teleology of nature in the Critique of the Power of Judgment and new perspectives on Kant's contributions to biology.